2021
DOI: 10.1001/jama.2021.7563
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of COVID-19 mRNA Vaccines in Pregnant and Lactating Women

Abstract: IMPORTANCE Pregnant women are at increased risk of morbidity and mortality from COVID-19 but have been excluded from the phase 3 COVID-19 vaccine trials. Data on vaccine safety and immunogenicity in these populations are therefore limited.OBJECTIVE To evaluate the immunogenicity of COVID-19 messenger RNA (mRNA) vaccines in pregnant and lactating women, including against emerging SARS-CoV-2 variants of concern. DESIGN, SETTING, AND PARTICIPANTS An exploratory, descriptive, prospective cohort study enrolled 103… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
296
3
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 340 publications
(382 citation statements)
references
References 26 publications
31
296
3
5
Order By: Relevance
“…52,53,54 It had been reported, compared to the wild type of USA-WA1/2020 SARS-CoV-2, the binding strength of neutralizing antibodies formed after Pfizer and Moderna vaccination was observed 3.5-and 6-fold lower for B.1.1.7 and B.1351, respectively. 12 Antibody resistance against B.1.1.7 and B.1351 was also reported by another study. 55 In addition, in UK, it also was reported that B.1.617.2 had overtaken B.1.1.7.…”
Section: Finding On Other Studiessupporting
confidence: 53%
See 1 more Smart Citation
“…52,53,54 It had been reported, compared to the wild type of USA-WA1/2020 SARS-CoV-2, the binding strength of neutralizing antibodies formed after Pfizer and Moderna vaccination was observed 3.5-and 6-fold lower for B.1.1.7 and B.1351, respectively. 12 Antibody resistance against B.1.1.7 and B.1351 was also reported by another study. 55 In addition, in UK, it also was reported that B.1.617.2 had overtaken B.1.1.7.…”
Section: Finding On Other Studiessupporting
confidence: 53%
“…19 Maternal antibody response has been described formed following vaccination. [11][12][13][14][15]17,18,20 Through vaccination, antibody response was formed rapidly; while through vaccination it was formed gradually. 20 The number of IgG and IgM against SARS-CoV-2 were significantly increased after vaccination.…”
Section: Main Findingmentioning
confidence: 99%
“…Las mujeres tuvieron una buena respuesta a las vacunas, produciendo los niveles necesarios de anticuerpos neutralizantes y células inmunitarias conocidas como células T de memoria, que pueden ofrecer una protección más duradera. La investigación también indica que las vacunas podrían ofrecer protección a los bebés nacidos de madres vacunadas (37,38) .…”
Section: La Vacuna Covid-19 En La Mujer Embara-zada La Mujer Lactante Y El Neonatounclassified
“…Second, COVID-19 vaccination has been rolled out in several countries and recent published reports indicate that vaccination induces robust IgA and IgG antibody responses with neutralizing activity in breast milk which may confer protection to breastfeeding infants [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%